2019
DOI: 10.20884/1.bion.2019.1.2.21
|View full text |Cite
|
Sign up to set email alerts
|

Terapi Audio dengan Murottal Alquran Terhadap Perilaku Anak Autis: Literature Review

Abstract: Introduction. Child auitism has a disorder in behavior, communication, social interaction and unstable emotions. Austism is a syndrome that results from complex muscle damage and neurodevelopmental disorders. Intervention to the behavior of children with autism can be done by providing murottal audio therapy Alquran.Objective. this study aimed to examine the effect of audio therapy with murottal Alquran on the behavior of austistic children.Methods. Article searches conducted electronically using several datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Children with autism often experience disturbances or problems in sleep patterns which if left unchecked can increase inappropriate behavior such as self-injury, aggression, and tantrums (Astuti & Maria, 2019). Handling sleep quality problems in children with autism is needed so that inappropriate behavior is more controlled (Anam et al, 2019). Audio therapy can be used as an option that is used as an effort to prevent and promote problems with sleep quality.…”
Section: Resultsmentioning
confidence: 99%
“…Children with autism often experience disturbances or problems in sleep patterns which if left unchecked can increase inappropriate behavior such as self-injury, aggression, and tantrums (Astuti & Maria, 2019). Handling sleep quality problems in children with autism is needed so that inappropriate behavior is more controlled (Anam et al, 2019). Audio therapy can be used as an option that is used as an effort to prevent and promote problems with sleep quality.…”
Section: Resultsmentioning
confidence: 99%
“…The number of people with autism is projected to increase as time goes by. The current estimation is about 4-6 per 10,000 births and a drastic increase may happen in 2030 with 60 per 10,000 births (Anam, Khasanah, & Isworo, 2019).…”
Section: Introductionmentioning
confidence: 85%
“…Interestingly, Anam et al (2019) found that audio therapy with murottal Al Quran can decrease disorders in emotion, communication and social interaction compared to music therapy (Anam et al, 2019). Based on research conducted by Faradilla et al (2020), there was a significant effect of listening to Ar-Rahman murottal in improving various clinical aspects of children with autism.…”
Section: Introductionmentioning
confidence: 99%
“…Saraf vagus membantu regulasi kecepatan denyut jantung, respirasi, kemampuan bicara, membawa impuls sensorik motorik ke tenggorokan, laring, jantung dan diafragma, sehingga efek suara pada anak autis dapat meningkatkan kemampuan komunikasi anak. Fungsi utama dari vagus adalah untuk fonasi/berbicara dan menelan (Mayrani & Hartati, 2013) (Mayrani & Hartati, 2013). Stimulus musik merangsang minat dan motivasi otak pada banyak anak autis (Freitas et al, 2022).…”
Section: Hasil Dan Pembahasanunclassified